Media Ethics : Epistemological Reading - djaafer, Mohammed (Journal of Social Sciences and Humanities, 2023)
The study of media ethics is one of the recent trends in media and communication research, it represents one of the most important cultural, social and value issues and problems that arise when talking about media practices and professional ethics, especially in that era of digital development and massive spread of traditional and new media. The media practitioner; a journalist, a broadcaster, or content maker in social media and so on; should be aware of the set of ethical principles and rules and the most important norms invoked when performing his mission, and thus his role in the service of society. The study presents an epistemological reading of the concept of media ethics. That is, the definition of Media ethics, the important approaches used to study it, and the normative theories developed by researchers in the field. Then the study presents the duties and obligations that require the media practitioner to balance between them while making various daily ethical decisions about what information to be provided to the public and what not to be.